Electroextraction of low-concentration redox-active heavy metals with E θ < 0 V from acid mine drainage - Ziyuan Huang; Chunhua Feng; Fengchang Wu; Zhenqing Shi; Yang Wang; Zhuoyu Zhang; Rimei Huang; Weijian Duan; Li Tian; Yijin Lv; Xinying Gong; Zhengjun Gong; et al. (Proceedings of the National Academy of Sciences, 2025)
Electrochemical recovery of heavy metals from acid mine drainage (AMD) offers a sustainable solution to global AMD contamination, yet remains challenged by thermodynamic and kinetic barriers in reducing redox-active metals with negative standard reduction potentials (E θ < 0 V), especially at low concentrations. Here, using Cd as a model system, we demonstrate that the formation of a metastable intermediate, Cd 2 SO 4 (OH) 2 , plays a crucial role in facilitating the efficient electrochemical reduction of low-concentration Cd(II) to metallic Cd 0 in acidic solutions. A combination of experimental and theoretical analyses reveals that in situ generated OH − at the cathode, in conjunction with bulk-phase SO 4 2− , drives the formation of this metal-inorganic complex, which mediates electron transfer by overcoming redox limitations. By optimizing flow dynamics and incorporating hierarchical electrode configurations, we enhance intermediate formation and achieve 96.81% Cd recovery from real AMD, with effluent Cd concentrations below 0.5 mg L −1 . Economic analysis estimates a net-positive return of 2.32 CNY per ton of treated AMD. Life cycle assessment further shows that the electroextraction process substantially outperforms lime neutralization with respect to all major environmental indicators. This work establishes a mechanistically driven, economically viable, and environmentally superior strategy for recovering valuable metals from AMD, advancing the prospects of circular resource recovery and sustainable wastewater management.